Pemetaan Literatur dalam Tesis Manajemen Informasi Perpustakaan - Dewi Maharani Rachmaningsih (Universitas Terbuka, 2022)
Scientific publication must be accountable for its sources, processes and results. This research is based on allegations of diversity citations used in research. These assumptions are influenced by research topics, knowledge development, technology, shifting of the library paradigm, librarian and student competencies. The purpose of this research is to mapping developments literature on thesis Library Information Management (MIP) students. The results of the study can be used as a reference consideration (secondary data) for further research. The research method uses bibliometric citation analysis. Citations are grouped with the help of co-classification mapping theory and will be elaborated descriptively based on predetermined indicators. The total data examined is 63 theses consisting of 2709 literatures. The Indicators used to analyze include the language of literature, the type of literature, the subject of literature, the list of authors along with the title of the essay and the list of publishers. The Citation analysis results include: (1). Analysis of the language of literature is to find out the variety of languages, it can be seen from the increasing use of foreign-language literature. (2). Analysis of the type of literature is to answer the development of literature. (3). Analysis of the subject used to mapping knowledge, the subject is influenced by the research perspective. (4). The essence of the results of the citation analysis using these indicators reveals that the citations in the Information Management and Library thesis of the 2007/2008-2012 / 2013 class vary. The mapping of the literature shows that annually experiencing development, change, and dynamic due to the main factor of technology and student ability.